Unraveling the Tax Puzzle: How CSR, GCG, and Firm Characteristics Affect Corporate Value through Tax Avoidance - Hendra Sanjaya Kusno; Sisca Santika; Wiwik Saraswati; Alvianita Gunawan Putri; Magda Elsyied (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Research Backgrounds: Governments rely on taxes as one of their main sources of income, which is used to fund social welfare and public spending. The hefty tax burden, however, frequently drives businesses to use tax planning tactics, such as tax avoidance, in order to lessen their tax liabilities while still operating within the law. In this situation, the value of the company may be impacted by company tax behavior, which may be influenced by corporate governance structures, CSR, and business characteristics. The connection between CSR, governance, company characteristics, tax evasion, and firm value is explored in this study. Introduction / Obejctives: Moreover, the study investigates if tax evasion plays a role in the link between CSR, GCG, firm attributes, and business worth. This research is notable for looking at tax avoidance as an intermediary function in the connection between corporate traits, governance systems, CSR, and firm value. Methods: The study uses a quantitative methodology and hypothesis testing to examine both direct and indirect correlations between the variables, using information from publicly traded firms. Findings/ Results: The findings suggest that tax evasion is largely unaffected by firm traits and GCG, but it is significantly impacted by CSR. Tax evasion, CSR, and GCG have no direct effect on a company's worth, but its characteristics do. CSR also has an indirect effect on company value via tax avoidance, but firm characteristics and GCG do not show a significant mediating influence via tax avoidance. Conclusions: These results emphasize how complicated CSR affects firm value via business tax legislation and imply that legislators and managers should take indirect routes into account while assessing a company's tax conduct and performance.